Psychobiological personality traits of children and adolescents with disorders of arousal. (February 2023) - Turner, Katherine; Castelnovo, Anna; Perogamvros, Lampros; Cloninger, Robert C.; Galbiati, Andrea; Bertolotti, Alessia; Proserpio, Paola; Terzaghi, Michele; Manni, Raffaele; Ferini Strambi, Luigi; Nobili, Lino; Manconi, Mauro; et al.
Abstract: Introduction: Disorders of arousal (DOA) are parasomnias that emerge from incomplete arousal out of Non-Rem Sleep (NREM) and lead to a broad variety of emotional and motor behaviours. Increasing evidence supports the hypothesis that specific psychopathological traits contribute to the multifactorial origin of these phenomena. The aim of the current multicenter study was to compare the personality profile of children and adolescents with and without DOA using the Junior Temperament and Character Inventory (JTCI). Methods: We enrolled 36 patients with a diagnosis of DOA (mean age of 11 ± 3 years, 64% males), and 36 healthy age and gender matched control subjects (mean age of 11.2 ± 3.6, years, 67% males). Their parents completed the Paris Arousal Disorder Severity Scale (PADSS), the Sleep Disturbance Scale for Children (SDSC) and the JTCI. Results: Patients with DOA reached significantly higher levels compared to their control group in total PADSS (p < 0.0001) and in total SDSC (p < 0.0001). They also displayed higher scores in novelty seeking (p = 0.005), harm avoidance (p = 0.01), self-transcendence (p = 0.006) JTCI subscales, and lower scores on the self-directedness subscale (p = 0.004). Conclusion: Our pediatric sample with DOA exhibited specific psychobiological personality traits compared to age and gender matched subjects without DOA. These results shed light on new possible etiopathogenetic mechanisms, as TCI traits have been linked to specific genetic variants and brain circuits, like the reward system. Prospective studies are required to assess the effect of targeted psychological/psychiatric treatment on DOA symptomatology.